Proteomic analysis of lipid body from the alkenone‐producing marine haptophyte alga Tisochrysis lutea. Issue 23 (2nd July 2015) - Shi, Qing; Araie, Hiroya; Bakku, Ranjith Kumar; Fukao, Yoichiro; Rakwal, Randeep; Suzuki, Iwane; Shiraiwa, Yoshihiro
Abstract : Lipid body (LB) is recognized as the cellular carbon and energy storage organelle in many organisms. LBs have been observed in the marine haptophyte alga Tisochrysis lutea that produces special lipids such as long‐chain (C37 ‐C40 ) ketones (alkenones) with 2–4 trans ‐type double bonds. In this study, we succeeded in developing a modified method to isolate LB from T. lutea . Purity of isolated LBs was confirmed by the absence of chlorophyll auto‐fluorescence and no contamination of the most abundant cellular protein ribulose‐1, 5‐bisphosphate carboxylase/oxygenase. As alkenones predominated in the LB by GC‐MS analysis, the LB can be more appropriately named as "alkenone body (AB)." Extracted AB‐containing proteins were analyzed by the combination of 1DE (SDS‐PAGE) and MS/MS for confident protein identification and annotated using BLAST tools at National Center for Biotechnology Information. Totally 514 proteins were identified at the maximum. The homology search identified three major proteins, V‐ATPase, a hypothetical protein EMIHUDRAFT_465517 found in other alkenone‐producing haptophytes, and a lipid raft‐associated SPFH domain‐containing protein. Our data suggest that AB of T. lutera is surrounded by a lipid membrane originating from either the ER or the ER‐derived four layer‐envelopes chloroplast and function as the storage site of alkenones and alkenes.